2020
DOI: 10.1007/978-3-030-42504-3_27
|View full text |Cite
|
Sign up to set email alerts
|

A Survey-Based Exploration of Users’ Awareness and Their Willingness to Protect Their Data with Smart Objects

Abstract: In the last years, the Internet of Things (IoT) and smart objects have become more and more popular in our everyday lives. While IoT contributes in making our everyday life more comfortable and easier, it also increases the threats to our privacy, as embedded sensors collect data about us and our environment. To foster the acceptance of IoT, privacy-preserving solutions are therefore necessary. While such solutions have already been proposed, most of them do not involve the users in their design. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Participants' weak understanding of privacy implications and potential inferences from data collection have been reported in other studies as well [7,67]. Authors in these studies also show users' common preferences in terms of transparency and awareness regarding security and privacy of data collection, disclosure and data practices from service providers [67,77,92,132,143]. The results of users' perceived privacy concerns are also reported in other contexts of smart environmentsin one study looking at factors influencing employees' willingness to share smartwatch-collected data [110] and in another one looking at privacy concerns of German users about mobile assistant robots [109].…”
Section: Privacy Attitudes In Smart Environmentssupporting
confidence: 52%
See 2 more Smart Citations
“…Participants' weak understanding of privacy implications and potential inferences from data collection have been reported in other studies as well [7,67]. Authors in these studies also show users' common preferences in terms of transparency and awareness regarding security and privacy of data collection, disclosure and data practices from service providers [67,77,92,132,143]. The results of users' perceived privacy concerns are also reported in other contexts of smart environmentsin one study looking at factors influencing employees' willingness to share smartwatch-collected data [110] and in another one looking at privacy concerns of German users about mobile assistant robots [109].…”
Section: Privacy Attitudes In Smart Environmentssupporting
confidence: 52%
“…Common concerns centre around data collection (including audio/visual), sharing and usage practices -feelings of data abuse, loss of control, inadequate protection, concerns about burglary and attacks from hackers and trust are relevant perceptions that can impact users' smart home acceptance. Opposing views are reported in several other studies [77,92,117,131], which have found that users do not perceive privacy concerns for personal data collected in smart homes, attributing their comfortability mainly to the trust in service provider companies, services' benefits [92,117,131] or lack of awareness and understanding of potential privacy issues in smart homes [77,92,143]. Participants' weak understanding of privacy implications and potential inferences from data collection have been reported in other studies as well [7,67].…”
Section: Privacy Attitudes In Smart Environmentsmentioning
confidence: 89%
See 1 more Smart Citation
“…P21 [54] conducted a questionnaire-oriented survey with two main objectives: (i) assessing users' inclination towards controlling data disclosure and (ii) preference for transparent privacy preservation based on users' needs in their homes. Their results reveal that users are cognizant of data collection and its privacy implications, and perceive themselves as capable of managing data collection.…”
Section: Privacy Focus In Iot Studiesmentioning
confidence: 99%
“…58.3 % of the studies reviewed had a traditional methodological approach towards user involvement, while 41.7 % had taken a more holistic approach. We coded traditional when the design focused mainly on a specific IoT technology/solution, such as in the case of Wickramasinghe and Reinhardt (2019) who investigate users' interacting with a particular privacypreserving solution dedicated to smart home environments to tailor the experience to their needs, rather than any wider human-human or human-service interaction. The code holistic was assigned when the methodological approach considered the whole IoT technology system as interconnected and evolving with factors in broader human dimensions.…”
Section: Human/user Involvementmentioning
confidence: 99%